Productive workers or better citizens? - DE MEYER, Arnoud Cyriel Leo (Institutional Knowledge at Singapore Management University, 2023)
How do different countries in the region view the wider societal function of higher education? If the goal is to train productive workers, then the content of higher education may be more tailored towards rote learning. If, however, the goal is to make workers more easily trainable as well as creative, then critical thinking might be a greater priority.